Wincenty Pol w audycjach Polskiego Radia Lublin w latach 1990-2017 - Żurakowska, Małgorzata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article discusses the radio broadcasts created in Polish Radio Lublin in the years 1990–2017 that introduce the life and works of Wincenty Pol, a patriot and a poet. Most of the programs are the effect of collaborations with the museum Wincenty Pol Manor House and scholars from the universities in Lublin. The author analyzes all the radio programs about the poet, proposing a different and innovative way of presenting the life and works of Pol. Two of the examined programs were created during family reunions of the poet’s family, and the others on the occasion of the openings of thematic exhibitions, e.g. of pipes or manuscripts. What is noteworthy is the citing of the correspondence that the poet received. The background invariably consists of the rooms of Wincenty Pol Manor House in the district of Kalinowszczyzna in Lublin. It is worth noting that the recurrence of the subject of Pol’s works in radio programs is occasional – in each case the recordings were prompted by the events taking place in the Manor House. When preparing thematic exhibitions, the curators often imported the exhibits from other national and foreign galleries or museums. The recordings eternalize the special moments when the permanent exhibition was enriched by the objects borrowed from other institutions. The role of the panel of experts in the radio programs was performed by literary scholars and the Museum employees. The picture of Pol that emerges from the recordings captures the author’s extraordinary personality, diligence and patriotism.